Sequelae of the Covid-19 pandemic in the performance of undergraduate students from a gender perspective - Castaño, Leticia; Farinós, José Emilio; Ibáñez, Ana M. (Journal of Management and Business Education, 2022)
Previous evidence concerning the unprecedented challenges brought about by the COVID-19 pandemic and the restrictive measures adopted shows that the pandemic caused a mental health deterioration, i.e. an increase in anxiety, stress and depression among university students. In particular, women have been affected to a greater extent by anxiety, depression and post-traumatic stress disorder problems during Covid-19. Our goal is to study undergraduate learning performance from a gender perspective in the period when the restrictions due to COVID-19 were still in force (first semester of academic year 2020/21). We use the final grade of undergraduate students that sat the final exam in the first exam session of three final year elective courses of the Facultat d’Economia (Universitat de València) from the academic year 2013/14 until 2020/21, for which the teaching method did not change during the pandemic, i.e. for which face-to-face learning was maintained. Our results show a significant drop in the results obtained by students during the first semester of 2020-21 centered on low-achieving students. However, female students perform better than male students in this group. In addition, our evidence suggests that better performers are more resilient irrespective of the student’s gender.